Van Hiele model and levels of geometric reasoning of triangles in Huancavelica students - Chavarria-Pallarco, Norman A. (2020)
The goal of the research was to determine if the application of the Dutch Van Hiele model to facilitates the advancement of the levels of geometric reasoning of triangles in students in the sixth cycle of regular basic education. The type of research was applied, using as specific methods: the experimental, the statistical and the hypothetical deductive; with a pre-experimental design, with a single group, made up of 29 students from the IE “César Vallejo Mendoza” from the populated center of Viñas, Acobambilla district, province and region of Huancavelica, a pretest and a posttest were applied to this group. The intentional non-probabilistic sampling, the processing and analysis of the results were carried out by applying the statistics. Likewise, the Student's t-test was used to contrast the hypotheses. As a result, we obtained that the application of the Van Hiele model made it easier to advance in the level of geometric reasoning (visualization, analysis and classification), because the calculated Student's t-test was -16, 632, so the null hypothesis was rejected, concluding that there is a significant difference in the means of the degrees of acquisition of the level of geometric reasoning of triangles before and after the application of the Van Hiele model.